Butanol Purified Food Allergy Herbal Formula-2 Has an Immunomodulating Effect ex-vivo in Pediatric Crohn's Disease Subjects - Chen, Xin; Lai, Joanne; Song, Ying; Yang, Nan; Gnjatic, Sacha; Gillespie, Virginia; Hahn, William; Chefitz, Ezra; Pittman, Nanci; Jossen, Jacqueline; Benkov, Keith; Dubinsky, Marla; et al. (Frontiers in Medicine, 2021)
Background: TNF-alpha has a major pathological role in Crohn’s disease (CD). In contrast, GM-CSF may be beneficial for its anti-inflammatory role in a subset of patients with CD with antibodies against GM-CSF. We developed butanol purified FAHF-2 (B-FAHF-2) by refining FAHF-2 which suppressed TNF-α production by human PBMCs and colonic mucosa and abrogated colitis in a murine model. We sought to examine the effect of B-FAHF-2 and the herbs that comprise it on TNF-α and GM-CSF production to develop an herbal therapy for CD. Methods: B-FAHF-2 was examined using HPLC and compared to the original formulation, FAHF-2. PBMCs from pediatric patients with CD were cultured with lipopolysaccharide and B-FAHF-2, individual herbs or medium alone. Biopsy specimens were cultured with or without B-FAHF-2. TNF-α and GM-CSF were measured by ELISA. B-FAHF-2 efficacy was tested in vivo in the CD45Rbhi transfer model. Results: B-FAHF-2 had a similar HPLC fingerprint as FAHF-2 but decreased TNF-αproduction by PBMCs and colonic mucosa from pediatric CD subjects at 20% of the FAHF-2 dose. B-FAHF-2 increased GM-CSF production by PBMCs and colonic mucosa from pediatric CD subjects. B-FAHF-2 increased GM-CSF production by PBMCs from a subset of CD subjects with antibodies to GM-CSF. Of B-FAHF-2’s herbal constituents, only Huang Bai suppressed TNF-α and increased GM-CSF production. In the murine model, B-FAHF-2 treatment alleviated colitis. Conclusions: B-FAHF-2 decreased TNF-α production by PBMCs and colonic mucosa of pediatric subjects at a lower dose than FAHF-2. B-FAHF-2 also increased GM-CSF production by PBMCs independent of antibodies. B-FAHF-2 may have a benefit in CD patients.